Efficacy of repeated cold water immersion on recovery after a simulated Rugby Union protocol - Barber, S.; Pattison, J.; Brown, F.; Hill, J. (The Journal of Strength and Conditioning Research, 2020)
Training and athletic competition frequently results in exercise-induced muscle damage (EIMD). The purpose of this study was to investigate the efficacy of repeated cold water immersion (CWI) on recovery after a simulated rugby union match. Sixteen male, club-level rugby players were matched for body mass and randomly assigned to either a CWI group or control (CON) group. After the simulated rugby match, the CWI group underwent 2 × 5-minute immersions at a temperature of 10° C separated by 2.5 minutes seated at room temperature, whereas the CON group remained seated for 15 minutes. Creatine kinase (CK), perceived muscle soreness, counter movement jump (CMJ), and maximal voluntary isometric contraction (MVIC) of the knee extensors were measured pre-exercise, postexercise, 24 and 48 hours after exercise. Large effect sizes were observed for muscle soreness at 24 and 48 hours after exercise with lower soreness values observed in the CWI group. Large effect sizes were observed for CMJ at all time points and at 24 and 48 hours post for MVIC with improved recovery of muscle function observed in the CWI group compared with the CON group. Last, a moderate effect size was observed for CK immediately after exercise, followed by large effect sizes at 24 and 48 hours after exercise, with CK concentration blunted in the CWI group. Overall, these findings provide some support for the use of CWI to enhance recovery from EIMD after a simulated rugby union match.